Anti-kyphosis smart bag detection of overweight bag load and improper spinal posture in army members when using work bags - Agung Hirawan; Muhammad Rey Renoult; Diyan Parwatiningtyas; Iqbal Ahmad Dahlan; Adhi Kusumadjati; Jofim Yordaniel Napitupulu (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2024)
Heavy field equipment owned by soldiers such as backpacks unknowingly makes soldiers move with the wrong body posture when in the field. Carrying a bag with a heavy load and the wrong posture (slouching), can cause abnormalities in the spine, such as slouching (kyphosis). Therefore, a posture therapy is needed with the method of habituation using a work bag with a load not exceeding 15 percent of the user's body weight and using it with the correct posture. This therapy / habituation is of course carried out outside of field training hours that do not ignore the use of heavy loads, for example in the office or anywhere else when carrying a bag. Seeing this, researchers are trying to create and develop an anti-kyphosis smart bag that can prevent and treat spinal deformities. After making the system, this smart bag was then tested quantitatively with the aim of seeing the qualification of the system's ability to detect excess bag weight, if the weight of the bag exceeds 15 percent of the user's body weight and the ability of the system to detect improper posture seen from the sensitivity level of the load cell sensor based on its placement position in the back area. The test was conducted on three respondents who were selected based on their height, namely 170 cm, 175 cm, and 182cm. The system calibration results show that the system works accurately, with a measuring error of 0% and effective sensor placement between the thoracic kyphosis and lumbar lordosis areas of the back, with the ability to detect a bend angle of at least 24.7°. Seeing the effectiveness of this anti-kyphosis smart bag, it is hoped that it can be a smart solution for TNI members in maintaining spinal posture to avoid kyphosis due to the habit of carrying excessive loads with the wrong body posture.